Gender Differences in Different Contexts - Alvinius, Aida (IntechOpen, 2017)
The development of gender differences as an area of research has been rapid over the last decades. Varieties of studies have focused on the gender differences as well as the similarities of women and men. The common purpose of the research attempt is to find out the possibilities and even the consequences of gender differences and the impact on human beings on one side, and social and cultural environment on the other. This book is an attempt to provide theoretical and empirical framework to better understand gender differences in various contexts and on different levels. Therefore, the contributions cover an array of themes that span from an individual level to an organizational and societal level.